Architecture, agency and ocean data science initiatives: Data-driven transformation of oceans governance - Lauren Drakopulos; Elizabeth Havice; Lisa Campbell (Earth System Governance, 2022)
The oceans are regarded as both relatively under-governed and understudied, especially at the global and regional scales. By mobilizing data with the express goal of improving oceans governance, ocean data science initiatives (ODSIs) are positioned to play a critical role in addressing and perhaps collapsing these gaps and to provide the “science we need for the ocean we want.” We argue that ODSIs are now critical oceans governance actors, to be examined as such. To this end, we have compiled a catalog of more than 150 global and regional ODSIs. Through a textual analysis of websites and public communications of a subset of these, we have created metadata about their practices. We examine ODSIs from the lens of three elements of Earth Systems Governance: normative frames, architecture and agency. ODSIs emerge from and evolve through, a range of institutional frameworks both inside and outside of formal policy forums, however, they are also transforming those frameworks through norms, institutions and practices which shape how data is valued, collected, organized, analyzed, and acted upon. As a result, ODSIs and their data products are not just mobilized by actors seeking to influence governance but are creating novel forms of agency and have become significant ocean governance actors in and of themselves. Thus, ODSIs both expand and blur the boundaries of architecture and agency. We conclude by considering how we might better understand ODSIs as governance actors through Earth Systems Governance, their role in shaping architecture and agency in governance relations and, in turn, the implications of integrating data and technology in an Earth Systems Governance framework.